THE DEVELOPMENT OF ACCOUNTING FOR REGULATORY PURPOSES BY THE FEDERAL POWER COMMISSION. - Kohler, E. L. (The Accounting Review, 1946)
In this article the author comments on a series of three articles entitled "Power Price Fixing," written by James L. Dohr, which were published in earlier issues of "Journal of Accountancy," as of January 1946. The articles discuss at some length the U.S. Federal Power Commission's decisions and those of the Montana and Arkansas utility commissions on the accounting practices of Montana Power Co. and Arkansas Power & Light Co. Each year the Federal Power Commission has published in a single volume the financial statements of the principal privately owned electric utilities of the U.S. An epitome of these statements was published for the year 1943 which brought out the striking changes that had taken place in the industry since January 1937, the date when the Uniform System of Accounts became effective. In the broad areas embraced by financial and business controls, accounting principles and policies have played a role that has increased greatly in importance during the past ten years. Accounting has become firmly entrenched as the language of business and of businessmen. Total assets, gross volume, net income are among the many terms that accountants have been able to keep within the confines of their art.